Prognostic Significance of EMVI in Rectal Cancer in a Tertiary Cancer Hospital in India - Pangarkar, Sayali Y.; Baheti, Akshay D.; Mistry, Kunal A.; Choudhari, Amit J.; Patil, Vasundhara R.; Ahuja, Ankita; Katdare, Aparna N.; Patil, Akshay B.; Ostwal, Vikas S.; Ramadwar, Mukta R.; Engineer, Reena Z.; Saklani, Avanish P. (Indian Journal of Radiology and Imaging, 2021)
Background Presence of extramural venous invasion (EMVI) is a poor prognostic factor for rectal cancer as per literature. However, India-specific data are lacking.Aim The aim of the study is to determine the prognostic significance of EMVI in locally advanced rectal cancer on baseline MRI.Materials and Methods We retrospectively reviewed 117 MRIs of operable non-metastatic locally advanced rectal cancers in a tertiary cancer institute. Three dedicated oncoradiologists determined presence or absence of EMVI, and its length and thickness, in consensus. These patients were treated as per standard institutional protocols and followed up for a median period of 37 months (range: 2–71 months). Kaplan-Meier curves (95% CI) were used to determine disease-free survival (DFS), distant-metastases free survival (DMFS), and overall survival (OS). Univariate analysis was performed by comparing groups with log-rank test.Results EMVI positive cases were 34/114 (29%). More EMVI-positive cases developed distant metastasis compared with EMVI-negative cases (14/34–41% vs. 22/83–26%). The difference, however, was not statistically significant (p = 0.146). After excluding signet-ring cell cancers (n = 14), EMVI showed significant correlation with DMFS (p = 0.046), but not with DFS or OS. The median thickness and length of EMVI was 6 and 14 mm, respectively in patients who developed distant metastasis, as compared with 5 and 11 mm in those who did not, although this difference was not statistically significant.Conclusion EMVI is a predictor of distant metastasis in locally advanced non-metastatic, non-signet ring cell rectal cancers. EMVI can be considered another high-risk feature to predict distant metastasis.
Keywords: extramural venous invasion; MRI; rectal cancer